QUALITY OF ACCOUNTING INFORMATION SYSTEMS, HR COMPETENCE AND GOVERNMENT INTERN CONTROL SYSTEM IN BELITUNG DISTRICT - Lisda, Ruslina; ari, ari anugrah (Jurnal Riset Bisnis dan Manajemen, 2023)
This Study aims to determine how much influence the quality of accounting information systems, human resource competencies and government internal control systems have on the performance of local government agencies. Data collection techniques were carried out through primary data with questionnaires. The population in this study were employees at the Dinas-Dinas di Pemerintah Kabupaten Belitung. The results show that partially the quality of the accounting information system affects the performance of the agency with an influence contribution of 25,1%, the competence of human resources affects the performance of the agency with a contribution of 17,3% influence, and the government’s internal control system affects the performance of the agency by influence contribution of 29%. The results of this study also show that simultaneously the quality of accounting information systems, human resource competencies and government intenral control systems have an effect on agency performance with a contribution of 71,4% influence.